Pengaruh Permaianan Bola Voli Mini Terhadap Peningkatan Kebugaran Jasmani Pecandu Narkoba - Kurnia Rismaningtyas (Universitas Negeri Semarang, 2016)
This study aims to answer the following questions: 1) the influence of a volleyball mini-game model to increase physical fitness of drug addicts in prisons Women Class II A Semarang in 2015. 2) How big contribution volleyball mini model of the game due to the improvement of physical fitness of drug addicts in prisons Women Class II A Semarang in 2015. . T test results obtained tcount for data post test of 2,420 with significance 0.022 <0.05, which means that the average physical fitness between the experimental and control groups after treatment was significantly different. Judging from an average of 35.79 in the experimental group and the control group of 32.92 indicates that the level of physical fitness of women prisoners IIA class drug addict treatment Semarang made a game of volleyball mini-game is better than that do not follow the game of volleyball mini , In the experimental group increased physical fitness significantly, evident from the value t = 6.541 with a significance value of 0.000 <0.05. It was concluded that: 1) Model mini volleyball games that do can improve the physical fitness of inmates in prisons Women Class II A Semarang. 2) In the experimental group showed that the model of a volleyball mini-game has a significant influence on the improvement of physical fitness on female inmates in prison Women drug addicts Class II A Semarang.